Sound-Quality Perception in Hair Dryers: Functional Near-Infrared Spectroscopy Evidence of Left-Lateralized Dorsolateral Prefrontal Cortex Activation - Shuang Xu; Zenggen Ren; Qingxing Qu (Applied Sciences)
This study investigates how the sound of a hair dryer influences users’ perceptions of its quality, using functional near-infrared spectroscopy (fNIRS) to measure prefrontal cortex (PFC) activation. Eighteen participants were involved in a within-subject evaluation experiment where they assessed the perceived quality of hair dryers with three different sound levels: no sound, low sound, and high sound. The results show that hair dryers with high sound levels were rated as having higher quality and caused greater increases in oxygenated hemoglobin (HbO) concentration in the dorsolateral prefrontal cortex (DLPFC) compared to soundless hair dryers. In contrast, when participants evaluated low-sound hair dryers, differential activation between the left and right hemispheres was observed, with increased left-brain activity. These findings highlight the significant role of multisensory factors, such as sound, in shaping product perception. Moreover, DLPFC activity, especially in the left hemisphere, emerges as a potential marker for evaluating product quality, contributing new insights to the understanding of sensory-driven decision-making in product evaluation.